The influence of image consciousness, materialism and compulsive spending on credit card usage intentions among youth - Nga, Joyce Koe Hwee *; Yong, Lisa H. L.; Rathakrishnan, S. (Emerald, 2011)
Purpose – This study aims to bridge the gap in the literature on consumer behaviours such as image consciousness, materialism and consumer spending on credit card usage intentions among Malaysian college students. Design/methodology/approach – A purposive sampling design was employed using a sample of 191 business and management students at a private higher education institution in Subang Jaya, Malaysia. An anonymous survey questionnaire was administered to the students. Structural equation modeling was then used to determine the validity of the path diagram and model fit. Findings – The findings of the study revealed that materialism is a partial mediator in the relationship between image consciousness and compulsive spending. The study also found that compulsive spending is not a mediator in the relationship between materialism and credit card usage intentions. However, compulsive spending does exert a sizable influence. Research limitations/implications – Future research is required to investigate whether family background has an impact on youth abilities to be more responsible and rational when undertaking more lavish lifestyles and credit. Practical implications – The implication of this study is that there needs to be more concerted efforts made in instilling credit card awareness and financial discipline among youth to avoid them falling into the debt trap at an early age. Originality/value – This study highlighted the existence of the credit card debt problem which can inhibit Malaysia’s vision to achieve a developed nation status in 2020